Determination of Carotenoid Bioavailability from Palm Oil Microencapsulation - Amanda, Ghaisani Shella; Syah Falaifi, Faqih Jibran; Mardiyati, Nur Lathifah (International Journal of Oil Palm, 2024)
Indonesia is the largest palm oil supplier in the world with a total production value of 20.97 million tons. Palm oil has a high content of carotenoids that act as antioxidants in the body. However, carotenoids and their derivatives have a conjugated structure that is unstable to oxidation and easily damaged. One of the optimal efforts to maintain the stability of carotenoids is by microencapsulation. This study aims to determine the efficiency of the palm oil microencapsulation method in maintaining the carotenoid components in it. The method used in this research is Systematic Literature Review based on Google Scholar, ScienceDirect, and Springer databases with predetermined inclusion criteria. The results showed that all palm oil microencapsulation methods produced good efficiency values and stable physicochemical characteristics of carotenoids even including other micronutrients such as vitamin E, moisture content, fatty acids, etc. which were also classified as stable. Overall, the supercritical carbon dioxide (SEDS) method produced the best quality while the spray drying method is a good choice for commercial microencapsulation. The conclusion of this study is that microencapsulation is able to protect the bioavailability of carotenoids in palm oil in a stable condition with values that are still within the standard range so as to produce better palm oil products as food ingredients for further use in a food product